2016
DOI: 10.1097/md.0000000000003701
|View full text |Cite|
|
Sign up to set email alerts
|

Lower serum uric acid level predicts mortality in dialysis patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 51 publications
7
65
1
Order By: Relevance
“…The adjusted HR at uric acid level ≤ 0.488 mmol/L compared with > 0.488 mmol/L was 1.24 (1.03-1.49) for all-cause mortality and 1.54 (1.15-2.07) for CVD mortality. Similar results were found by Bae et al [136]. The authors proposed that elevated uric acid levels among HD patients may be a surrogate marker for better nutritional status, as these patients also had higher serum phosphate and BMI [135].…”
Section: Latif Et Al Reviewed Dopps Data and Found That Higher Uric supporting
confidence: 78%
“…The adjusted HR at uric acid level ≤ 0.488 mmol/L compared with > 0.488 mmol/L was 1.24 (1.03-1.49) for all-cause mortality and 1.54 (1.15-2.07) for CVD mortality. Similar results were found by Bae et al [136]. The authors proposed that elevated uric acid levels among HD patients may be a surrogate marker for better nutritional status, as these patients also had higher serum phosphate and BMI [135].…”
Section: Latif Et Al Reviewed Dopps Data and Found That Higher Uric supporting
confidence: 78%
“…Nutritional parameters are closely associated with each other, and high uric acid concentrations have been linked to protein intake or high nPCR, greater BMI, and higher serum concentrations of albumin, creatinine and phosphorus [18][19][20][21][22][23]. The major source of uric acid is purine-rich foods such as meats, seafood and purine-rich vegetables, all of which also include high protein.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, protein-rich diets tend to contain large quantities of purines [25], and higher uric acid concentrations may represent better nutritional status in the ESRD population [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study in Japan demonstrated that low uric acid level (<4.6 mg/dl in men and <3.3 mg/dl in women) can increase CVD mortality . Recently, several studies have shown that a low uric acid level was significantly associated with increased all‐cause mortality in patients undergoing dialysis . The uric acid has an antioxidant effect , and it has been demonstrated that hypouricemia can injure the endothelium and induce oxidative stress–related disease such as hypertension, diabetes mellitus, and kidney disease .…”
mentioning
confidence: 99%